ras gene Amplification and malignant transformation. - Pulciani, S (1985)
Morphologic transformation of NIH 3T3 mouse cells occurs upon transfection of these cells with large amounts (greater than or equal to 10 micrograms) of recombinant DNA molecules carrying the normal human H-ras-1 proto-oncogene. We provide experimental evidence indicating that transformation of these NIH 3T3 cells results from the combined effect of multiple copies of the H-ras-1 proto-oncogene rather than from spontaneous mutation of one of the transfected H-ras-1 clones (E. Santos, E.P. Reddy, S. Pulciani, R.J. Feldman, and M. Barbacid, Proc. Natl. Acad. Sci. USA 80:4679-4683, 1983). Levels of H-ras-1 RNA and p21 expression are highly elevated in the NIH 3T3 transformants, and in those cases examined, these levels correlate with the malignant properties of these cells. We have also investigated the presence of amplified ras genes in a variety of human carcinomas. In 75 tumor biopsies, we found amplification of the human K-ras-2 locus in one carcinoma of the lung. These results indicate that ras gene amplification is an alternative pathway by which ras genes may participate in the development of human neoplasia.